2000
DOI: 10.1001/archsurg.135.2.175
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of Body Temperature to Normothermia During Resuscitation Following Trauma-Hemorrhage Improves the Depressed Cardiovascular and Hepatocellular Functions

Abstract: Hypothesis: Rewarming the body to 37°C during resuscitation following trauma-hemorrhage has salutary effects on cardiovascular and hepatocellular functions. Design, Interventions, and Main Outcome Measures: Male rats underwent laparotomy (trauma induced) and were then bled to and maintained at a mean arterial pressure of 40 mm Hg until 40% of the maximum shed blood volume was returned in the form of Ringer lactate solution. Rats were exposed to ambient temperature and allowed to become hypothermic during hemor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 23 publications
1
9
0
1
Order By: Relevance
“…Clinical retrospective analysis has suggested that hypothermia is associated with poor outcome in trauma patients. [1][2][3] This supports the recommendations that hypothermia should be avoided in trauma patients. [4,5] The US Emergency War Surgery guidelines require early recognition, aggressive prevention, and treatment of hypothermia (including heat lamps, warmed fluids, forced air heating, and warm water immersion).…”
Section: Introductionsupporting
confidence: 74%
“…Clinical retrospective analysis has suggested that hypothermia is associated with poor outcome in trauma patients. [1][2][3] This supports the recommendations that hypothermia should be avoided in trauma patients. [4,5] The US Emergency War Surgery guidelines require early recognition, aggressive prevention, and treatment of hypothermia (including heat lamps, warmed fluids, forced air heating, and warm water immersion).…”
Section: Introductionsupporting
confidence: 74%
“…However, some recent studies failed to confirm the beneficial effects of hypothermia in patients with traumatic brain injury (24,25). Indeed, hypothermia has been demonstrated to be associated also with several deleterious effects such as acidosis (3), coagulopathy (26), hemodynamic instability (3,16,(27)(28)(29), cardiac arrhythmias (16,27,28,30), ventilatory instability (31-33), reduction of leukocytes and neutrophils (3,34), thrombocytopenia (16,27,34), endotoxemia (35), infectious complications (16,27,28,34,36), and increase of lipase and amylase levels (16,34,37). Most of these adverse effects have been reported only in association with prolonged mild hypothermia.…”
Section: Discussionmentioning
confidence: 99%
“…In klinischen Studien scheint die Hypothermie mit einer höheren Mortalität assoziiert. Die Gründe hierfür sind wahrscheinlich eine Einschränkung der linksventrikulären Funktion und des HZV sowie eine regionale, hepatische Perfusionsstörung unter Hypothermie [76,77]. Ein weiterer Aspekt ist der negative Effekt der Hypothermie auf das Gerinnungssystem; eine hypotherme Koagulopathie ist mit einem schlechten Outcome korreliert [48].…”
Section: Kontrollierte Hypothermieunclassified